A Quick Perusal to Open Educational Resources (OERs) Presence for the Past One Decade through Bibliometric Lens with Special Reference to SpringerLink - KUMAR, AMIT; Deka, Manashjyoti (Qualitative and Quantitative Methods in Libraries, 2022)
The concept of Open Educational Resources (OER) is a topic of growing interest for researchers as a powerful contribution to improving the quality and openness of the education system. The goal of this particular research is to review the literature on the concept of ‘Open Educational Resources (OER)’ through bibliometric lens, published by SpringerLink for the past one decade. The study provides a detailed concept and definition of open educational resources and review of related literature. The bibliographic details were retrieved from SpringerLink database ( https://link,springer.com ) by using keywords such as ‘open educational resources,’ ‘OER’. The bibliographical details of 1824 literatures published were recorded in MS-Excel 2019 sheet. The paper shows that during the period of 2011-2020, different categories of literature were published and Chapter has occupied the most literature published by Springer Link. The present paper also reveals the year-wise growth, authorship pattern, author productivity, most productive journals, highest contributed institutions and geographical distribution of the research output. The Annual Growth Rate (AGR), Compound Annual Growth Rate (CAGR), Relative Growth Rate (RGR), Doubling Time of literature followed by the indicators such as degree of collaboration; collaborative index and collaboration coefficient have been calculated and presented.